Essentials of visual interpretation - Reynolds, Rachel R., author.
1 online resource (xv, 219 pages)
Keywords: "Essentials of Visual Interpretation teaches students to talk and write critically about visual media and to examine how evolving visual environments, media, and technologies affect human self-understanding and culture formation. Lively and accessibly written chapters provide a solid foundation in the tools and ideas of visual meaning, familiarizing readers with a growing, cross-cultural subfield and preparing them to pursue thoughtful work in a variety of related disciplines. The authors include rich examples and illustrations-ranging from cave paintings to memes, from optical science to visual analytics, from ancient pictographs to smart phones-that engage students with the fascinating complexity of visual interpretation. Each chapter introduces students to key terms and concepts relevant to visual analysis, with ideas for short individual or group exercises to enhance understanding. The book is ideal as a primer in visual analysis and visual communication for introductory students in courses within communication studies, cultural studies, semiotics, media studies, and visual anthropology"--